Menumbuhkan Ekonomi Kreatif di Kalangan Jemaat Warga Dewasa GKJ Klasis Sala dengan Memanfaatkan Limbah Kulit Buah Naga - Sundari, Sundari; Nugroho, Novemy Triyandari (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The creative economy is an economic concept that relies on creativity, innovation, and the utilization of ideas as the main factors in creating economic added value. The main objective of the creative economy is to optimize the potential of human resources in producing products and services that are unique and highly competitive. Many of the congregants are housewives who are still very productive in producing a work, which is able to support the creative economy, from here then the Community Service Team of Duta Bangsa University tries to provide training on making jenang dodol snacks made from dragon fruit skin. The aim of providing assistance to partners in order to be able to foster creative economies with the business of processing dragon fruit peel waste into healthy food, namely jenang dodol.